Cheater Detection for Randomized Response-Techniques: Derivation, Analyses and Applications - Sascha Feth; Monika Frenger; Werner Pitsch; Patrick Schmelzeisen (universaar - Universitätsverlag des Saarlandes, 2017)
Finding out how often an embarrassing characteristic exists in a population is accompanied by numerous problems that are due in particular to false answers as a consequence of social undesirability. The oldest of the techniques developed to compensate for these distortions is the Randomized Response Technique which is currently still the most widely used, evaluated and researched technique in the field of sensitive subjects. Although this technique guarantees complete security for the person being questioned and therefore opens up options for answering even threatening questions honestly, even here "cheating" occurs in terms of not complying with the instructions. This volume describes the mathematical derivation of techniques to detect the extent to which this "cheating" occurs. It also provides analyses on the process characteristics and extends these analyses to include practical advice on how to use this process flexibly. A general solution is developed for various forms of "cheating" for the first time. – – Will man herausfinden, wie häufig eine peinliche Eigenschaft in einer Population auftritt, gehen damit etliche Probleme einher, die vor allem auf verfälschte Antworten in Folge sozialer Erwünschtheit zurückgehen. Die älteste der Techniken, die entwickelt wurden um diese Verzerrungen zu kompensieren ist die Randomized Response-Technik, die auch derzeit noch die am weitesten verbreitete und am meisten evaluierte und erforschte Technik im Feld sensitiver Themen darstellt. Obwohl diese Technik den Befragten vollständige Sicherheit garantiert und damit die Möglichkeit eröffnet, auch auf bedrohliche Fragen ehrlich zu antworten, tritt auch dabei "Cheating" auf im Sinne der Nicht-Beachtung der Instruktionen. Der vorliegende Band beschreibt die mathematische Herleitung von Techniken zur Erkennung des Ausmaßes, in dem dieses "Cheating" auftritt. Er stellt darüber hinaus Analysen zu Eigenschaften des Verfahrens dar und erweitert diese Analysen um praktische Hinweise zum flexiblen Einsatz dieser Verfahren. Dabei wird erstmals für unterschiedliche Formen des "Cheatings" eine allgemeine Lösung entwickelt.
urn:nbn:de:bsz:291-universaar-1617; hdl:20.500.11880/31009
Keywords: 300; Response behavior; statistics